Electoral Power Structure of Islamic Parties in Reform Era Indonesia - Romli, Lili (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
The Islamic political parties in the Reform era grew up exceeding the period of Parliamentary Democracy. In the electoral competition during the Reform era, Islamic political parties did not receive adequate votes. The votes won by Islamic parties tend to go down from election to election. There are several factors that have caused the Islamic party to fail to win the support of Muslim votes. First, Islamic parties are fragmented and internal conflict. Second, Muslim voters do a change in ideological orientation which no chooses an Islamic party but a nationalist party. Third, nationalist parties accommodate Muslim aspirations by forming Islamic organizations. Fourth, the crisis of leadership of the Islamic party. Fifth, the absence of a real party program. To improve the electoral, Islamic parties must concern on programs to improve people's welfare, democratization, eradicate corruption, and realize social justice. The leader of Islamic parties must be exemplary, visionary, integrity, and rooted in the community.